Acoustical Analysis of the National Theatre of Costa Rica by means of its Room Impulse Responses - Delgado-Castro, Alejandro (2024)
In this work, the main hall of the National Theatre of Costa Rica is studied in order to obtain an acoustical characterisation of this particular space, based on its estimated room impulse responses, which are measured using an 8-inch loudspeaker as the sound source. These impulse responses are obtained in mono and stereo formats and then used to estimate a set of acoustical parameters, which are then used to estimate the reverberation time, the clarity and definition of the voice and music, as well as other details such as the warmth and brilliance of the room, providing a basis for the acoustical characterisation of the hall. Given the unique features of the National Theatre and its importance as the prime venue for performing arts in Costa Rica, the analysis presented here constitutes a record of its room acoustics and provides a perspective that could help understanding the way in which sound propagates inside this peculiar hall.